A study on benchmarking techniques in sipcot industrial park, perundurai - S, Pradeepa; S, Ramya (Journal of Management and Science, 2013)
The objective of this paper is to examine the effectiveness of benchmarking for the improvement in products, services & processes. This paper contributes by expanding benchmarking literature, as a result of exploring the factors that will contribute best practice in benchmarking process in SIPCOT. Implementing benchmarking is one of the ways to create a sense of urgency by telling them where are, how good they have to be, and what have to do to get there. The study has been conducted in various companies in SIPCOT Industrial park, Perundurai. Process benchmarking acts as the critical methodology for generating a portfolio of improvement projects which can systematically increase organization performance effectiveness, efficiency, and economy as it continues in its journey toward performance excellence.